Antibacterial ceramic products with improved aesthetics and manufacturing method thereof

KR103018323B1Active Publication Date: 2026-09-11KOREA INST OF CERAMIC ENG & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020230168944
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2026-09-11
Estimated Expiration
2043-11-29

Smart Images

  • Figure 112023133455482-PAT00001_ABST
    Figure 112023133455482-PAT00001_ABST
Patent Text Reader

Abstract

A method for manufacturing an antibacterial ceramic product is provided. The method for manufacturing the antibacterial ceramic product may include the steps of: manufacturing a body by pressure molding a body composition and then performing a first sintering; forming a masking layer by coating an engobe composition comprising frit, feldspar, silica, kaolin, and zircon onto the body; forming an antibacterial glaze layer by coating a glaze composition comprising frit, kaolin, zinc oxide (ZnO), and color pigment onto the masking layer; performing a second sintering of a structure on the body in which the masking layer and the antibacterial glaze layer are formed; and improving the antibacterial properties of the antibacterial glaze layer by photo-sintering the antibacterial glaze layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an antibacterial ceramic product and a method for manufacturing the same, and more specifically, to an antibacterial ceramic product with enhanced aesthetic appeal through color expression and a method for manufacturing the same. Background Technology

[0002] In order to enhance the functionality and value of ceramic products such as household tableware, sanitary ware, and ceramic tiles, antimicrobial materials such as silver paste and copper film have conventionally been coated on the surface of ceramic products.

[0003] However, when antibacterial properties are imparted to ceramic products using the method described above, the unit cost of the product increases due to additional processes, and a problem arises where the antibacterial function gradually disappears as the coating peels off over time.

[0004] Therefore, the inventors intend to develop a ceramic product that can impart antibacterial properties solely through a glaze coating without additional processes and can continuously maintain these antibacterial properties until the ceramic product is discarded. The problem to be solved

[0005] The technical problem that the present invention aims to solve is to provide an antibacterial ceramic product and a method for manufacturing the same.

[0006] Another technical problem that the present invention aims to solve is to provide an antibacterial ceramic product with improved aesthetic appeal and a method for manufacturing the same.

[0007] Another technical problem that the present invention aims to solve is to provide an antibacterial ceramic product that is easy to apply to various products and a method for manufacturing the same.

[0008] The technical problems that the present invention aims to solve are not limited to those described above. means of solving the problem

[0009] To solve the above technical problems, the present invention provides a method for manufacturing an antibacterial ceramic product.

[0010] According to one embodiment, the method for manufacturing the antibacterial ceramic product may include the steps of: manufacturing a body by pressure molding a body composition and then performing a first sintering; forming a masking layer by coating an engobe composition comprising frit, feldspar, silica, kaolin, and zircon onto the body; forming an antibacterial glaze layer by coating a glaze composition comprising frit, kaolin, zinc oxide (ZnO), and color pigment onto the masking layer; performing a second sintering of a structure on the body in which the masking layer and the antibacterial glaze layer are formed; and improving the antibacterial properties of the antibacterial glaze layer by photo-sintering the antibacterial glaze layer.

[0011] According to one embodiment, depending on the type of color pigment, the sintering temperature in the secondary sintering step and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer in the step of improving antibacterial properties may be controlled to improve both the antibacterial properties of the antibacterial glaze layer against Staphylococcus aureus and Escherichia coli.

[0012] According to one embodiment, when the color pigment includes a pigment exhibiting a brown color, the sintering temperature in the secondary sintering step is controlled to 1100℃, and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer is 23 J / cm² 2 It may include being controlled by.

[0013] According to one embodiment, the color pigment may include iron oxide (Fe2O3).

[0014] According to one embodiment, when the color pigment includes a pigment exhibiting a black color, the sintering temperature in the secondary sintering step is controlled to 1100℃, and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer is 45 J / cm² 2 It may include being controlled by.

[0015] According to one embodiment, the color pigment may include cobalt iron chromium oxide (Co(Fe,Cr)2O4).

[0016] According to one embodiment, when the color pigment includes a pigment exhibiting a blue color, the sintering temperature in the secondary sintering step is controlled to 1150℃, and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer is 0.72 J / cm² 2 It may include being controlled by.

[0017] According to one embodiment, the color pigment may include cobalt aluminum oxide (CoAl2O4).

[0018] According to one embodiment, the light sintering of the antibacterial glaze layer may include a method of irradiating white light using a xenon lamp.

[0019] According to one embodiment, as the antibacterial glaze layer is photo-sintered, the surface roughness of the antibacterial glaze layer is reduced, and the gloss, contact angle, and hardness are improved.

[0021] To solve the above technical problems, the present invention provides an antibacterial ceramic product.

[0022] According to one embodiment, the antibacterial ceramic product comprises a body comprising limestone, clay, feldspar, pyrophyllite, and kaolin; a masking layer disposed on the body comprising frit, feldspar, silica, kaolin, and zircon; and an antibacterial glaze layer disposed on the masking layer comprising frit, kaolin, zinc oxide (ZnO), and color pigment, wherein the antibacterial glaze layer may have antibacterial properties against both Staphylococcus aureus and Escherichia coli.

[0023] According to one embodiment, the antibacterial glaze layer may comprise 85-90 wt% frit, 7-12 wt% kaolin, 2-5 wt% zinc oxide, and 2-5 wt% color pigment. Effects of the invention

[0024] A method for manufacturing an antibacterial ceramic product according to an embodiment of the present invention may include the steps of: manufacturing a body by pressure molding a body composition and then performing a first sintering; forming a masking layer by coating an engobe composition comprising frit, feldspar, silica, kaolin, and zircon onto the body; forming an antibacterial glaze layer by coating a glaze composition comprising frit, kaolin, zinc oxide (ZnO), and a color pigment onto the masking layer; performing a second sintering of a structure formed on the body with the masking layer and the antibacterial glaze layer formed thereon; and improving the antibacterial properties of the antibacterial glaze layer by photo-sintering the antibacterial glaze layer. Accordingly, an antibacterial ceramic product can be provided in which high antibacterial properties can be continuously maintained as well as aesthetic appeal is enhanced through a colored surface. Brief explanation of the drawing

[0025] FIG. 1 is a flowchart illustrating a method for manufacturing an antibacterial ceramic product according to an embodiment of the present invention. FIG. 2 is a drawing for explaining an antibacterial ceramic product according to an embodiment of the present invention. Specific details for implementing the invention

[0026] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the attached drawings. However, the technical concept of the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete, and to ensure that the concept of the present invention is sufficiently conveyed to those skilled in the art.

[0027] In this specification, when a component is described as being on another component, it means that it may be formed directly on the other component or that a third component may be interposed between them. Additionally, in the drawings, the thicknesses of the films and regions are exaggerated for the effective description of the technical content.

[0028] Additionally, although terms such as first, second, third, etc. have been used to describe various components in various embodiments of this specification, these components should not be limited by such terms. Accordingly, what is referred to as the first component in one embodiment may be referred to as the second component in another embodiment.

[0029] Each embodiment described and exemplified herein also includes its complementary embodiment. Additionally, the term 'and / or' in this specification is used to mean including at least one of the components listed before and after it.

[0030] In the specification, singular expressions include plural expressions unless the context clearly indicates otherwise. Furthermore, terms such as "include" or "have" are intended to specify the existence of the features, numbers, steps, components, or combinations thereof described in the specification, and should not be understood as excluding the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0031] Furthermore, in describing the present invention below, if it is determined that a detailed description of related known functions or configurations could unnecessarily obscure the essence of the invention, such detailed description will be omitted.

[0033] FIG. 1 is a flowchart for explaining a method for manufacturing an antibacterial ceramic product according to an embodiment of the present invention, and FIG. 2 is a drawing for explaining an antibacterial ceramic product according to an embodiment of the present invention.

[0034] Referring to FIGS. 1 and 2, a body (100) can be manufactured by pressure molding a substrate composition and then performing a first sintering (S100). More specifically, the substrate composition is ball milled for 24 hours, then dried at a temperature of 80°C for 24 hours, and 250 kg / cm² 2 The body (100) can be manufactured by applying a uniaxial pressure to the disk at a pressure of 300 mm and pi, and by primary sintering at a temperature of 1150°C for 50 minutes. According to one embodiment, the body composition may include 8-15 wt% limestone, 20-25 wt% clay, 40-45 wt% kaolin, 10-15 wt% pyrophyllite, and 5-15 wt% kaolin.

[0035] A masking layer (200) can be formed by coating an engobe composition on the body (100) (S200). More specifically, the engobe composition can be wet-mixed for 24 hours, aged for 3 hours to remove bubbles, coated on the body (100) using a spray coating method, and then dried for 6 hours to form the masking layer (200). According to one embodiment, the engobe composition may comprise 50-70 wt% frit, 0-10 wt% feldspar, 10-20 wt% silica, 10-20 wt% kaolin, and 2-5 wt% zircon. Additionally, according to one embodiment, the masking layer (200) may be formed with a thickness of 100 μm.

[0036] An antibacterial glaze layer (300) can be formed by coating a glaze composition onto the masking layer (200) (S300). More specifically, the glaze composition can be wet-mixed for 24 hours, aged for 3 hours to remove bubbles, coated onto the masking layer (200) using a spray coating method, and then dried for 6 hours to form the antibacterial glaze layer (300). According to one embodiment, the glaze composition may comprise 85-90 wt% frit, 7-12 wt% kaolin, 2-5 wt% zinc oxide (ZnO), and 2-5 wt% color pigment. Additionally, according to one embodiment, the antibacterial glaze layer (300) may be formed with a thickness of 150 μm.

[0037] The above antibacterial glaze layer (300) may have antibacterial properties due to the zinc oxide. More specifically, the above antibacterial glaze layer (300) may have antibacterial properties against Staphylococcus aureus (S. Aureus) and Escherichia coli (E. Coli). In addition, the above antibacterial glaze layer (300) may exhibit color due to the color pigment.

[0038] A structure having the masking layer (200) and the antibacterial glaze layer (300) formed on the body (100) can be sintered a second time (S400). As described above, when the antibacterial glaze layer (300) contains zinc oxide, the glaze composition is formed by fusing it into a vitreous state on the body (100) and the masking layer (200) during the second sintering process, so that the antibacterial properties of the antibacterial glaze layer (300) can be continuously maintained until the ceramic product is discarded.

[0039] After the above second sintering step (S400), the antibacterial glaze layer (300) can be light-sintered to improve the antibacterial properties of the antibacterial glaze layer (300) (S500). According to one embodiment, the light-sintering of the antibacterial glaze layer (300) can be performed by irradiating white light using a xenon lamp.

[0040] As described above, when the antibacterial glaze layer (300) includes the color pigment, there is an advantage in that the aesthetic appeal can be enhanced by the color pigment, but a problem may arise in that the antibacterial properties are degraded. However, when light sintering is performed on the antibacterial glaze layer (300), the degradation of antibacterial properties caused by the color pigment can be minimized, so that not only the aesthetic appeal of the antibacterial glaze layer (300) but also high antibacterial properties can be maintained. In addition, the surface roughness of the antibacterial glaze layer (300) can be reduced and the gloss, contact angle, and hardness can be improved through light sintering.

[0041] According to one embodiment, in order for the antibacterial glaze layer (300) to have high antibacterial properties against both Staphylococcus aureus (S. Aureus) and Escherichia coli (E. Coli), the sintering temperature in the secondary sintering step (S400) and the energy value per area of ​​light irradiated on the antibacterial glaze layer (300) in the step (S500) of improving the antibacterial properties can be controlled according to the type of color pigment.

[0042] More specifically, when the color pigment includes a pigment exhibiting a brown color, the sintering temperature in the secondary sintering step is controlled to 1100℃, and the energy value per area of ​​light irradiated onto the antibacterial glaze layer (300) is 23 J / cm² 2 It can be controlled in this way. For example, a pigment that exhibits a brown color may contain iron oxide (Fe2O3). In contrast, if the sintering temperature in the secondary sintering step and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer (300) are controlled differently from what is described above, a problem may arise in which it has high antibacterial properties against either Staphylococcus aureus (S. Aureus) or Escherichia coli (E. Coli), but low antibacterial properties against the other.

[0043] Alternatively, if the color pigment includes a pigment exhibiting a black color, the sintering temperature in the secondary sintering step is controlled to 1100℃, and the energy value per area of ​​light irradiated onto the antibacterial glaze layer (300) is 45 J / cm² 2It can be controlled in this way. For example, a pigment that exhibits a black color may include cobalt iron chromium oxide (Co(Fe,Cr)2O4). In contrast, if the sintering temperature in the secondary sintering step and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer (300) are controlled differently from what is described above, a problem may arise in which it has high antibacterial properties against either Staphylococcus aureus (S. Aureus) or Escherichia coli (E. Coli), but low antibacterial properties against the other.

[0044] Alternatively, if the color pigment includes a pigment exhibiting a blue color, the sintering temperature in the secondary sintering step is controlled to 1150℃, and the energy value per area of ​​light irradiated onto the antibacterial glaze layer (300) is 0.72 J / cm² 2 It can be controlled in this way. For example, a pigment that exhibits a blue color may include cobalt aluminum oxide (CoAl2O4). In contrast, if the sintering temperature in the secondary sintering step and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer (300) are controlled differently from what is described above, a problem may arise in which it has high antibacterial properties against either Staphylococcus aureus (S. Aureus) or Escherichia coli (E. Coli), but low antibacterial properties against the other.

[0046] The antibacterial ceramic product and the method for manufacturing the same according to the embodiments of the present invention have been described above. Below, specific experimental examples and characteristic evaluation results of the antibacterial ceramic product and the method for manufacturing the same according to the embodiments of the present invention are described.

[0047] Experiment Example 1

[0048] Experiment to derive the sintering temperature in the secondary sintering step (S400) and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer in the step (S500) to improve antibacterial properties, in order to have high antibacterial properties against both Staphylococcus aureus (S. Aureus) and Escherichia coli (E. coli), when the color pigment includes a pigment (Fe2O3) exhibiting a brown color.

[0050] Preparation of antibacterial ceramic products according to Experimental Example 1-1 (Ex 1-1)

[0051] A body composition comprising 8–15 wt% limestone, 20–25 wt% clay, 40–45 wt% feldspar, 10–15 wt% pyrophyllite, and 5–15 wt% kaolin is ball milled for 24 hours, then dried at a temperature of 80°C for 24 hours, and 250 kg / cm² 2 A body was manufactured by uniaxially pressing the disk with a pressure of 300 mm and 1150°C for 50 minutes, and sintering at a temperature of 1150°C.

[0052] An engobe composition comprising 50~70 wt% frit, 0~10 wt% feldspar, 10~20 wt% silica, 10~20 wt% kaolin, and 2~5 wt% zircon was wet-mixed for 24 hours, aged for 3 hours to remove bubbles, and then the aged engobe composition was coated onto the body using a spray coating method and dried for 6 hours to form a masking layer.

[0053] A glaze composition comprising 85~90 wt% frit, 7~12 wt% kaolin, and 2~5 wt% zinc oxide (ZnO) was wet-mixed for 24 hours, aged for 3 hours to remove air bubbles, and then the aged glaze composition was coated onto the masking layer using a spray coating method and dried for 6 hours to form an antibacterial glaze layer.

[0054] An antibacterial ceramic product according to Experimental Example 1-1 was manufactured by secondarily sintering a structure having the masking layer and the antibacterial glaze layer formed on the body at a temperature of 1100°C for 40 minutes, and then irradiating white light using a xenon lamp (photosintering) the antibacterial glaze layer. More specifically, the white light irradiation using a xenon lamp (photosintering) was performed under conditions of 1~10 ms On-time, 1~20 ms Off-time, 1 s Total time, and 0~50 Pulse.

[0056] Preparation of antibacterial ceramic products according to Experimental Example 1-2 (Ex 1-2)

[0057] A glaze composition was prepared according to the method described in Experimental Example 1-1 above, comprising 85-90 wt% frit, 7-12 wt% kaolin, 2-5 wt% zinc oxide (ZnO), and 2-5 wt% iron oxide (Fe2O3). More specifically, a glaze composition was used in which the iron oxide (Fe2O3) content was 25 wt% relative to zinc oxide (ZnO).

[0059] Preparation of antibacterial ceramic products according to Experimental Example 1-3 (Ex 1-3)

[0060] A glaze composition was prepared according to the method described in Experimental Example 1-1 above, comprising 85-90 wt% frit, 7-12 wt% kaolin, 2-5 wt% zinc oxide (ZnO), and 2-5 wt% iron oxide (Fe2O3). More specifically, a glaze composition was used in which the iron oxide (Fe2O3) content was 50 wt% relative to zinc oxide (ZnO).

[0061] division Second firing temperature Whether Fe2O3 is contained in the glaze composition Ratio of Fe2O3 content to ZnO in glaze composition Experiment Example 1-1 (Ex 1-1) 1100℃ X 0 wt% Experimental Example 1-2 (Ex 1-2) 1100℃ O 25 wt% Experimental Example 1-3 (Ex 1-3) 1100℃ O 50 wt%

[0062] Various characteristics were measured for each of the antibacterial ceramic products according to Experimental Examples 1-1 to 1-3 above, with varying energy values ​​per unit area of ​​white light irradiated during the photo-sintering stage after secondary sintering. The measured results are summarized in Tables 2 to 4 below, where S1 represents the state without photo-sintering and S2 represents 0.72 J / cm²2 A state in which photo-sintering is performed using white light having an energy value per area, S3 is 23 J / cm 2 A state in which photo-sintering is performed through white light having an energy value per area, S4 is 45 J / cm 2 This shows the measurement results for a state in which light sintering is performed using white light having an energy value per area.

[0063] Ex 1-1 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 99.9 99.9 99.9 99.9 E.Coli 99.9 99.9 99.9 99.9 Roughness (μm) 0.136 0.128 0.125 0.124 Gloss (Gu) 62 66 67 65 Contact angle (°) 81 89 87 88 Surface hardness (GPa) 5.2 5.6 5.4 5.5

[0064] Ex 1-2 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 79.4 84.3 87.5 86.2 E.Coli 60.1 69.0 70.2 68.8 Roughness (μm) 0.134 0.122 0.124 0.125 Gloss (Gu) 61 65 66 67 Contact angle (°) 79 86 89 91 Surface hardness (GPa) 5.1 5.6 5.5 5.6

[0065] Ex 1-3 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 61.8 78.0 79.6 76.3 E.Coli 46.0 60.1 63.1 61.2 Roughness (μm) 0.245 0.187 0.190 0.192 Gloss (Gu) 48 56 57 59 Contact angle (°) 65 76 73 78 Surface hardness (GPa) 4.6 5.1 5.5 5.3

[0066] As can be seen in Tables 3 and 4, when the glaze composition contains iron oxide (Fe2O3), it is confirmed that antibacterial properties, gloss, contact angle, and surface hardness are improved, while roughness is reduced by photosintering. Furthermore, regardless of the iron oxide (Fe2O3) content relative to zinc oxide (ZnO), 23 J / cm² 2 When light sintering with energy per unit area is performed (S3), it can be confirmed that it has the highest antibacterial properties against both Staphylococcus aureus (S. Aureus) and Escherichia coli (E. Coli).

[0068] Preparation of antibacterial ceramic products according to Experimental Example 1-4 (Ex 1-4)

[0069] It was manufactured by the method according to Experimental Example 1-1 described above, but by sintering at a temperature of 1150℃ in the second sintering step.

[0071] Preparation of antibacterial ceramic products according to Experimental Example 1-5 (Ex 1-5)

[0072] It was manufactured by the method according to Experimental Example 1-2 described above, but by sintering at a temperature of 1150℃ in the second sintering step.

[0074] Preparation of antibacterial ceramic products according to Experimental Example 1-6 (Ex 1-6)

[0075] It was manufactured by the method according to Experimental Examples 1-3 described above, but by sintering at a temperature of 1150℃ in the second sintering step.

[0076] division Second firing temperature Whether Fe2O3 is contained in the glaze composition Ratio of Fe2O3 content to ZnO in glaze composition Experimental Example 1-4 (Ex 1-4) 1150℃ X 0 wt% Experimental Example 1-5 (Ex 1-5) 1150℃ O 25 wt% Experimental Example 1-6 (Ex 1-6) 1150℃ O 50 wt%

[0077] Various characteristics were measured for each of the antibacterial ceramic products according to Experimental Examples 1-4 to 1-6 above, with varying energy values ​​per unit area of ​​white light irradiated during the photo-sintering stage after secondary sintering. The measured results are summarized in Tables 6 to 8 below, where S1 represents the state without photo-sintering and S2 represents 0.72 J / cm² 2 A state in which photo-sintering is performed using white light having an energy value per area, S3 is 23 J / cm 2 A state in which photo-sintering is performed through white light having an energy value per area, S4 is 45 J / cm 2 This shows the measurement results for a state in which light sintering is performed using white light having an energy value per area.

[0078] Ex 1-4 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 99.9 99.9 99.9 99.9 E.Coli 99.9 99.9 99.9 99.9 Roughness (μm) 0.189 0.152 0.150 0.149 Gloss (Gu) 59 67 65 66 Contact angle (°) 75 90 89 88 Surface hardness (GPa) 5.2 5.7 5.6 5.9

[0079] Ex 1-5 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 78.5 83.4 81.3 82.5 E.Coli 56.0 66.1 67.3 65.9 Roughness (μm) 0.188 0.163 0.165 0.166 Gloss (Gu) 56 69 69 70 Contact angle (°) 71 89 90 92 Surface hardness (GPa) 5.1 5.7 5.4 5.6

[0080] Ex 1-6 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 54.0 70.1 70.5 71.8 E.Coli 38.9 57.5 56.9 56.7 Roughness (μm) 0.176 0.156 0.152 0.150 Gloss (Gu) 56 68 67 68 Contact angle (°) 71 86 90 92 Surface hardness (GPa) 4.9 5.5 5.6 5.7

[0081] As can be seen in Tables 7 and 8, when the glaze composition contains iron oxide (Fe2O3), it can be observed that antibacterial properties, gloss, contact angle, and surface hardness are improved, while roughness is reduced by photosintering. However, when the content of iron oxide (Fe2O3) relative to zinc oxide (ZnO) is 25 wt% (Ex 1-5), the value is 0.72 J / cm² 2 The highest antibacterial properties against Staphylococcus aureus (S. Aureus) were observed due to light sintering (S2), with 23 J / cm² 2 The antibacterial properties against E. coli are highest due to light sintering (S3), and in the case where the iron oxide (Fe2O3) content relative to zinc oxide (ZnO) is 50 wt% (Ex 1-6), 45 J / cm² 2The antibacterial properties against Staphylococcus aureus (S. Aureus) are highest due to light sintering (S4), with 0.72 J / cm 2 It can be confirmed that the antibacterial properties against E. coli are highest when the photo-sintering (S2) is performed. That is, when secondary sintering is performed at a temperature of 1150°C, it can be seen that the energy per unit area of ​​light that maximizes antibacterial properties is different.

[0082] Consequently, as can be seen from Experimental Example 1, when the color pigment includes a brown pigment (Fe2O3), in order to possess high antibacterial properties against both Staphylococcus aureus (S. Aureus) and Escherichia coli (E. coli), the sintering temperature during the secondary sintering step is controlled to 1100℃, and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer is 23 J / cm². 2 It can be seen that it must be controlled by.

[0084] Experiment Example 2

[0085] Experiment to derive the sintering temperature in the secondary sintering step (S400) and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer in the step (S500) to improve antibacterial properties, in order to have high antibacterial properties against both Staphylococcus aureus (S. Aureus) and Escherichia coli (E. coli), when the color pigment includes a pigment (Co(Fe,Cr)2O4) exhibiting a black color.

[0087] Preparation of antibacterial ceramic products according to Experimental Example 2-1 (Ex 2-1)

[0088] A body composition comprising 8–15 wt% limestone, 20–25 wt% clay, 40–45 wt% feldspar, 10–15 wt% pyrophyllite, and 5–15 wt% kaolin is ball milled for 24 hours, then dried at a temperature of 80°C for 24 hours, and 250 kg / cm² 2A body was manufactured by uniaxially pressing the disk with a pressure of 300 mm and 1150°C for 50 minutes, and sintering at a temperature of 1150°C.

[0089] An engobe composition comprising 50~70 wt% frit, 0~10 wt% feldspar, 10~20 wt% silica, 10~20 wt% kaolin, and 2~5 wt% zircon was wet-mixed for 24 hours, aged for 3 hours to remove bubbles, and then the aged engobe composition was coated onto the body using a spray coating method and dried for 6 hours to form a masking layer.

[0090] A glaze composition comprising 85~90 wt% frit, 7~12 wt% kaolin, and 2~5 wt% zinc oxide (ZnO) was wet-mixed for 24 hours, aged for 3 hours to remove air bubbles, and then the aged glaze composition was coated onto the masking layer using a spray coating method and dried for 6 hours to form an antibacterial glaze layer.

[0091] An antibacterial ceramic product according to Experimental Example 2-1 was manufactured by secondarily sintering a structure having the masking layer and the antibacterial glaze layer formed on the body at a temperature of 1100°C for 40 minutes, and then irradiating white light using a xenon lamp (photosintering) the antibacterial glaze layer. More specifically, the white light irradiation using a xenon lamp (photosintering) was performed under conditions of 1~10 ms On-time, 1~20 ms Off-time, 1 s Total time, and 0~50 Pulse.

[0093] Preparation of antibacterial ceramic products according to Experimental Example 2-2 (Ex 2-2)

[0094] A glaze composition was prepared according to the method described in Experimental Example 2-1 above, comprising 85-90 wt% frit, 7-12 wt% kaolin, 2-5 wt% zinc oxide (ZnO), and 2-5 wt% cobalt iron chromium oxide (Co(Fe,Cr)2O4). More specifically, a glaze composition was used in which the content of cobalt iron chromium oxide (Co(Fe,Cr)2O4) was 25 wt% relative to zinc oxide (ZnO).

[0096] Preparation of antibacterial ceramic products according to Experimental Example 2-3 (Ex 2-3)

[0097] A glaze composition was prepared according to the method described in Experimental Example 2-1 above, comprising 85-90 wt% frit, 7-12 wt% kaolin, 2-5 wt% zinc oxide (ZnO), and 2-5 wt% cobalt iron chromium oxide (Co(Fe,Cr)2O4). More specifically, a glaze composition was used in which the content of cobalt iron chromium oxide (Co(Fe,Cr)2O4) was 50 wt% relative to zinc oxide (ZnO).

[0098] division Second firing temperature Whether Co(Fe,Cr)2O4 is contained in the glaze composition Ratio of Co(Fe,Cr)2O4 content to ZnO in glaze composition Experiment Example 2-1 (Ex 2-1) 1100℃ X 0 wt% Experiment Example 2-2 (Ex 2-2) 1100℃ O 25 wt% Experiment Example 2-3 (Ex 2-3) 1100℃ O 50 wt%

[0099] Various characteristics were measured for each of the antibacterial ceramic products according to Experimental Examples 2-1 to 2-3 above, with varying energy values ​​per unit area of ​​white light irradiated during the photo-sintering stage after secondary sintering. The measured results are summarized in Tables 10 to 12 below, where S1 represents the state without photo-sintering and S2 represents 0.72 J / cm² 2 A state in which photo-sintering is performed using white light having an energy value per area, S3 is 23 J / cm 2 A state in which photo-sintering is performed through white light having an energy value per area, S4 is 45 J / cm 2 This shows the measurement results for a state in which light sintering is performed using white light having an energy value per area.

[0100] Ex 2-1 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 99.9 99.9 99.9 99.9 E.Coli 99.9 99.9 99.9 99.9 Roughness (μm) 0.136 0.118 0.120 0.121 Gloss (Gu) 62 70 71 69 Contact angle (°) 81 91 94 96 Surface hardness (GPa) 5.2 5.6 5.5 5.8

[0101] Ex 2-2 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 74.9 85.2 84.7 86.4 E.Coli 61.0 65.0 65.5 66.5 Roughness (μm) 0.143 0.110 0.116 0.121 Gloss (Gu) 60 70 78 68 Contact angle (°) 0 94 92 91 Surface hardness (GPa) 5.1 5.7 5.8 5.9

[0102] Ex 2-3 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 68.1 70.2 70.5 71.8 E.Coli 44.4 51.8 51.4 52.0 Roughness (μm) 0.254 0.175 0.176 0.181 Gloss (Gu) 49 56 53 55 Contact angle (°) 68 82 83 88 Surface hardness (GPa) 4.9 5.2 5.1 5.0

[0103] As can be seen in Tables 11 and 12, when the glaze composition contains cobalt iron chromium oxide (Co(Fe,Cr)2O4), it is confirmed that antibacterial properties, gloss, contact angle, and surface hardness are improved, while roughness is reduced, by photosintering. Furthermore, regardless of the content of cobalt iron chromium oxide (Co(Fe,Cr)2O4) relative to zinc oxide (ZnO), 45 J / cm² 2 When light sintering with energy per unit area is performed (S4), it can be confirmed that it has the highest antibacterial properties against both Staphylococcus aureus (S. Aureus) and Escherichia coli (E. Coli).

[0105] Preparation of antibacterial ceramic products according to Experimental Example 2-4 (Ex 2-4)

[0106] It was manufactured by the method according to Experimental Example 2-1 described above, but by sintering at a temperature of 1150℃ in the second sintering step.

[0108] Preparation of antibacterial ceramic products according to Experimental Example 2-5 (Ex 2-5)

[0109] It was manufactured by the method according to Experimental Example 1-2 described above, but by sintering at a temperature of 1150℃ in the second sintering step.

[0111] Preparation of antibacterial ceramic products according to Experimental Example 2-6 (Ex 2-6)

[0112] It was manufactured by the method according to Experimental Example 2-3 described above, but by sintering at a temperature of 1150℃ in the second sintering step.

[0113] division Second firing temperature Whether Co(Fe,Cr)2O4 is contained in the glaze composition Ratio of Co(Fe,Cr)2O4 content to ZnO in glaze composition Experiment Example 2-4 (Ex 2-4) 1150℃ X 0 wt% Experimental Example 2-5 (Ex 2-5) 1150℃ O 25 wt% Experiment Example 2-6 (Ex 2-6) 1150℃ O 50 wt%

[0114] Various characteristics were measured for each of the antibacterial ceramic products according to Experimental Examples 2-4 to 2-6 above, with varying energy values ​​per unit area of ​​white light irradiated during the photo-sintering stage after secondary sintering. The measured results are summarized in Tables 14 to 16 below, where S1 is the state without photo-sintering and S2 is 0.72 J / cm²2 A state in which photo-sintering is performed using white light having an energy value per area, S3 is 23 J / cm 2 A state in which photo-sintering is performed through white light having an energy value per area, S4 is 45 J / cm 2 This shows the measurement results for a state in which light sintering is performed using white light having an energy value per area.

[0115] Ex 2-4 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 99.9 99.9 99.9 99.9 E.Coli 99.9 99.9 99.9 99.9 Roughness (μm) 0.189 0.144 0.151 0.162 Gloss (Gu) 59 65 66 67 Contact angle (°) 75 88 85 90 Surface hardness (GPa) 5.2 5.5 5.6 5.7

[0116] Ex 2-5 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 75.8 82.2 81.7 83.0 E.Coli 54.7 63.8 65.1 62.4 Roughness (μm) 0.171 0.148 0.146 0.141 Gloss (Gu) 51 58 59 60 Contact angle (°) 72 90 87 91 Surface hardness (GPa) 5.0 5.4 5.5 5.5

[0117] Ex 2-6 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 52.9 61.8 65.5 64.9 E.Coli 39.8 45.2 46.2 47.0 Roughness (μm) 0.162 0.139 0.137 0.140 Gloss (Gu) 55 62 61 62 Contact angle (°) 72 87 88 92 Surface hardness (GPa) 5.1 5.5 5.6 5.7

[0118] As can be seen in Tables 15 and 16, when the glaze composition contains cobalt iron chromium oxide (Co(Fe,Cr)2O4), it can be observed that antibacterial properties, gloss, contact angle, and surface hardness are improved, while roughness is reduced, by photosintering. However, when the content of cobalt iron chromium oxide (Co(Fe,Cr)2O4) relative to zinc oxide (ZnO) is 25 wt% (Ex 2-5), the value is 45 J / cm² 2 The highest antibacterial properties against Staphylococcus aureus (S. Aureus) are observed due to light sintering (S4), with 23 J / cm 2 The antibacterial properties against E. coli are highest when the photo-sintering (S3) is performed, and when the content of cobalt iron chromium oxide (Co(Fe,Cr)2O4) relative to zinc oxide (ZnO) is 50 wt% (Ex 2-6), the value is 23 J / cm² 2 The highest antibacterial properties against Staphylococcus aureus (S. Aureus) are observed due to light sintering (S3), with 45 J / cm² 2 It can be confirmed that the antibacterial properties against E. coli are highest when the photo-sintering (S4) is performed. That is, when secondary sintering is performed at a temperature of 1150°C, it can be seen that the energy per unit area of ​​light that maximizes antibacterial properties is different.

[0119] Consequently, as can be seen from Experimental Example 2, when the color pigment includes a black pigment (Co(Fe,Cr)2O4), in order to possess high antibacterial properties against both Staphylococcus aureus and Escherichia coli, the sintering temperature during the secondary sintering step is controlled to 1100℃, and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer is 45 J / cm² 2 It can be seen that it must be controlled by.

[0121] Experiment Example 3

[0122] Experiment to derive the sintering temperature in the secondary sintering step (S400) and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer in the step (S500) to improve antibacterial properties, in order to have high antibacterial properties against both Staphylococcus aureus (S. Aureus) and Escherichia coli (E. coli), when the color pigment includes a pigment (CoAl2O4) exhibiting a blue color.

[0124] Preparation of antibacterial ceramic products according to Experimental Example 3-1 (Ex 3-1)

[0125] A body composition comprising 8–15 wt% limestone, 20–25 wt% clay, 40–45 wt% feldspar, 10–15 wt% pyrophyllite, and 5–15 wt% kaolin is ball milled for 24 hours, then dried at a temperature of 80°C for 24 hours, and 250 kg / cm² 2 A body was manufactured by uniaxially pressing the disk with a pressure of 300 mm and 1150°C for 50 minutes, and sintering at a temperature of 1150°C.

[0126] An engobe composition comprising 50~70 wt% frit, 0~10 wt% feldspar, 10~20 wt% silica, 10~20 wt% kaolin, and 2~5 wt% zircon was wet-mixed for 24 hours, aged for 3 hours to remove bubbles, and then the aged engobe composition was coated onto the body using a spray coating method and dried for 6 hours to form a masking layer.

[0127] A glaze composition comprising 85~90 wt% frit, 7~12 wt% kaolin, and 2~5 wt% zinc oxide (ZnO) was wet-mixed for 24 hours, aged for 3 hours to remove air bubbles, and then the aged glaze composition was coated onto the masking layer using a spray coating method and dried for 6 hours to form an antibacterial glaze layer.

[0128] An antibacterial ceramic product according to Experimental Example 3-1 was manufactured by secondarily sintering a structure having the masking layer and the antibacterial glaze layer formed on the body at a temperature of 1100°C for 40 minutes, and then irradiating white light using a xenon lamp (photosintering) the antibacterial glaze layer. More specifically, the white light irradiation using a xenon lamp (photosintering) was performed under conditions of 1~10 ms On-time, 1~20 ms Off-time, 1 s Total time, and 0~50 Pulse.

[0130] Preparation of antibacterial ceramic products according to Experimental Example 3-2 (Ex 3-2)

[0131] A glaze composition was prepared according to the method described in Experimental Example 3-1 above, comprising 85-90 wt% frit, 7-12 wt% kaolin, 2-5 wt% zinc oxide (ZnO), and 2-5 wt% cobalt aluminum oxide (CoAl2O4). More specifically, a glaze composition was used in which the content of cobalt aluminum oxide (CoAl2O4) was 25 wt% relative to zinc oxide (ZnO).

[0133] Preparation of antibacterial ceramic products according to Experimental Example 3-3 (Ex 3-3)

[0134] A glaze composition was prepared according to the method described in Experimental Example 3-1 above, comprising 85-90 wt% frit, 7-12 wt% kaolin, 2-5 wt% zinc oxide (ZnO), and 2-5 wt% cobalt aluminum oxide (CoAl2O4). More specifically, a glaze composition was used in which the content of cobalt aluminum oxide (CoAl2O4) was 50 wt% relative to zinc oxide (ZnO).

[0135] division Second firing temperature Whether CoAl2O4 is contained in the glaze composition Ratio of CoAl2O4 content to ZnO in glaze composition Experiment Example 3-1 (Ex 3-1) 1100℃ X 0 wt% Experiment Example 3-2 (Ex 3-2) 1100℃ O 25 wt% Experiment Example 3-3 (Ex 3-3) 1100℃ O 50 wt%

[0136] Various characteristics were measured for each of the antibacterial ceramic products according to Experimental Examples 3-1 to 3-3 above, with varying energy values ​​per unit area of ​​white light irradiated during the photo-sintering stage after secondary sintering. The measured results are summarized in Tables 18 to 20 below, where S1 represents the state without photo-sintering and S2 represents 0.72 J / cm² 2 A state in which photo-sintering is performed using white light having an energy value per area, S3 is 23 J / cm 2 A state in which photo-sintering is performed through white light having an energy value per area, S4 is 45 J / cm 2 This shows the measurement results for a state in which light sintering is performed using white light having an energy value per area.

[0137] Ex 3-1 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 99.9 99.9 99.9 99.9 E.Coli 99.9 99.9 99.9 99.9 Roughness (μm) 0.136 0.121 0.120 0.119 Gloss (Gu) 62 68 69 67 Contact angle (°) 81 92 93 94 Surface hardness (GPa) 5.2 5.6 5.5 5.6

[0138] Ex 3-2 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 63.8 70.1 68.3 69.2 E.Coli 48.1 56.4 57.2 55.8 Roughness (μm) 0.145 0.122 0.125 0.128 Gloss (Gu) 60 68 67 64 Contact angle (°) 77 92 94 97 Surface hardness (GPa) 5.0 5.6 5.6 5.7

[0139] Ex 3-3 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 51.0 62.4 60.1 58.8 E.Coli 35.2 41.2 42.5 44.8 Roughness (μm) 0.198 0.162 0.161 0.158 Gloss (Gu) 56 62 61 64 Contact angle (°) 70 89 90 90 Surface hardness (GPa) 4.9 5.6 5.4 5.4

[0140] As can be seen in Tables 19 and 20, when the glaze composition contains cobalt aluminum oxide (CoAl2O4), it can be observed that antibacterial properties, gloss, contact angle, and surface hardness are improved, while roughness is reduced, by photosintering. However, when the content of cobalt aluminum oxide (CoAl2O4) relative to zinc oxide (ZnO) is 25 wt% (Ex 3-5), the value is 0.72 J / cm² 2 The highest antibacterial properties against Staphylococcus aureus (S. Aureus) were observed due to light sintering (S2), with 23 J / cm² 2 The antibacterial properties against E. coli are highest due to light sintering (S3), and when the content of cobalt aluminum oxide (CoAl2O4) relative to zinc oxide (ZnO) is 50 wt% (Ex 3-6), the value is 0.72 J / cm² 2 The highest antibacterial properties against Staphylococcus aureus (S. Aureus) are observed due to light sintering (S2), with 45 J / cm² 2 It can be confirmed that the antibacterial properties against E. coli are highest when the photo-sintering (S4) is performed. That is, when secondary sintering is performed at a temperature of 1100°C, it can be seen that the energy per unit area of ​​light that maximizes antibacterial properties is different.

[0142] Preparation of antibacterial ceramic products according to Experimental Example 3-4 (Ex 3-4)

[0143] It was manufactured by the method according to Experimental Example 3-1 described above, but by sintering at a temperature of 1150℃ in the second sintering step.

[0145] Preparation of antibacterial ceramic products according to Experimental Example 3-5 (Ex 3-5)

[0146] It was manufactured by the method according to Experimental Example 3-2 described above, but by sintering at a temperature of 1150℃ in the second sintering step.

[0148] Preparation of antibacterial ceramic products according to Experimental Example 3-6 (Ex 3-6)

[0149] It was manufactured by the method according to Experimental Example 3-3 described above, but by sintering at a temperature of 1150℃ in the second sintering step.

[0150] division Second firing temperature Whether CoAl2O4 is contained in the glaze composition Ratio of CoAl2O4 content to ZnO in glaze composition Experiment Example 3-4 (Ex 3-4) 1150℃ X 0 wt% Experiment Example 3-5 (Ex 3-5) 1150℃ O 25 wt% Experiment Example 3-6 (Ex 3-6) 1150℃ O 50 wt%

[0151] Various characteristics were measured for each of the antibacterial ceramic products according to Experimental Examples 3-4 to 3-6 above, with varying energy values ​​per unit area of ​​white light irradiated during the photo-sintering stage after secondary sintering. The measured results are summarized in Tables 22 to 24 below, where S1 represents the state without photo-sintering and S2 represents 0.72 J / cm² 2 A state in which photo-sintering is performed using white light having an energy value per area, S3 is 23 J / cm 2 A state in which photo-sintering is performed through white light having an energy value per area, S4 is 45 J / cm 2 This shows the measurement results for a state in which light sintering is performed using white light having an energy value per area.

[0152] Ex 3-4 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 99.9 99.9 99.9 99.9 E.Coli 99.9 99.9 99.9 99.9 Roughness (μm) 0.189 0.155 0.154 0.151 Gloss (Gu) 59 68 68 69 Contact angle (°) 75 91 90 92 Surface hardness (GPa) 5.2 5.6 5.7 5.4

[0153] Ex 3-5 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 62.0 68.1 67.2 67.0 E.Coli 45.1 49.8 47.8 48.0 Roughness (μm) 0.208 0.178 0.177 0.181 Gloss (Gu) 54 60 57 61 Contact angle (°) 69 89 90 88 Surface hardness (GPa) 5.0 5.3 5.4 5.4

[0154] Ex 3-6 S1 S2 S3 S4 Antimicrobial properties (%) S. Aureus 56.2 63.8 61.2 62.8 E.Coli 39.5 44.5 42.7 43.8 Roughness (μm) 0.198 0.168 0.166 0.164 Gloss (Gu) 54 61 60 62 Contact angle (°) 72 83 87 85 Surface hardness (GPa) 5.1 5.5 5.4 5.6

[0155] As can be seen in Tables 23 and 24, when the glaze composition contains cobalt aluminum oxide (CoAl2O4), it is confirmed that antibacterial properties, gloss, contact angle, and surface hardness are improved, while roughness is reduced, by photosintering. Furthermore, regardless of the content of cobalt aluminum oxide (CoAl2O4) relative to zinc oxide (ZnO), 0.72 J / cm² 2 When light sintering with energy per unit area is performed (S2), it can be confirmed that it has the highest antibacterial properties against both Staphylococcus aureus (S. Aureus) and Escherichia coli (E. Coli).

[0156] Consequently, as can be seen from Experimental Example 3, when the color pigment includes a blue pigment (CoAl2O4), in order to possess high antibacterial properties against both Staphylococcus aureus and Escherichia coli, the sintering temperature during the secondary sintering step is controlled to 1150℃, and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer is 0.72 J / cm² 2 It can be seen that it must be controlled by.

[0158] Although the present invention has been described in detail using preferred embodiments, the scope of the invention is not limited to specific embodiments and should be interpreted by the appended claims. Furthermore, those skilled in the art will understand that many modifications and variations are possible without departing from the scope of the invention. Explanation of the symbols

[0159] 100: Body 200: Masking layer 300: Antibacterial glaze layer

Claims

Claim 1 A method for manufacturing an antibacterial ceramic product comprising: a step of manufacturing a body by pressure molding a substrate composition and then performing a first sintering; a step of forming a masking layer by coating an engobe composition comprising frit, feldspar, silica, kaolin, and zircon onto the body; a step of forming an antibacterial glaze layer by coating a glaze composition comprising frit, kaolin, zinc oxide (ZnO), and a color pigment onto the masking layer; a step of performing a second sintering of a structure formed on the body with the masking layer and the antibacterial glaze layer formed thereon; and a step of improving the antibacterial properties of the antibacterial glaze layer by photo-sintering the antibacterial glaze layer, wherein the color pigment comprises cobalt iron chromium oxide (Co(Fe,Cr)2O4). Claim 2 A method for manufacturing an antibacterial ceramic product according to claim 1, comprising controlling the energy value per area of ​​light irradiated onto the antibacterial glaze layer in the step of improving the antibacterial properties and the sintering temperature in the step of improving the antibacterial properties, thereby improving the antibacterial properties of the antibacterial glaze layer against both Staphylococcus aureus and Escherichia coli. Claim 3 In claim 2, the sintering temperature in the secondary sintering step is controlled to 1100℃, and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer is 45 J / cm² 2 A method for manufacturing an antimicrobial ceramic product including being controlled by Claim 4 A method for manufacturing an antibacterial ceramic product according to claim 1, wherein the color pigment exhibits a black color. Claim 5 A method for manufacturing an antibacterial ceramic product according to claim 1, wherein the light sintering of the antibacterial glaze layer is performed by irradiating white light using a xenon lamp. Claim 6 A method for manufacturing an antibacterial ceramic product comprising: a step of manufacturing a body by pressure molding a substrate composition and then performing a first sintering; a step of forming a masking layer by coating an engobe composition comprising frit, feldspar, silica, kaolin, and zircon onto the body; a step of forming an antibacterial glaze layer by coating a glaze composition comprising frit, kaolin, zinc oxide (ZnO), and a color pigment onto the masking layer; a step of performing a second sintering of a structure formed on the body with the masking layer and the antibacterial glaze layer formed thereon; and a step of improving the antibacterial properties of the antibacterial glaze layer by photo-sintering the antibacterial glaze layer, wherein the color pigment comprises cobalt aluminum oxide (CoAl2O4). Claim 7 A method for manufacturing an antibacterial ceramic product according to claim 6, comprising controlling the energy value per area of ​​light irradiated onto the antibacterial glaze layer in the step of improving the antibacterial properties and the sintering temperature in the step of improving the antibacterial properties, thereby improving the antibacterial properties of the antibacterial glaze layer against both Staphylococcus aureus and Escherichia coli. Claim 8 In claim 7, the sintering temperature in the secondary sintering step is controlled to 1150℃, and the energy value per unit area of ​​light irradiated onto the antibacterial glaze layer is 0.72 J / cm² 2 A method for manufacturing an antimicrobial ceramic product including being controlled by Claim 9 A method for manufacturing an antibacterial ceramic product according to claim 6, wherein the color pigment exhibits a blue color. Claim 10 A method for manufacturing an antibacterial ceramic product according to claim 6, wherein as the antibacterial glaze layer is photo-sintered, the surface roughness of the antibacterial glaze layer is reduced and the gloss, contact angle, and hardness are improved. Claim 11 An antibacterial ceramic product comprising: a body comprising limestone, clay, feldspar, pyrophyllite, and kaolin; a masking layer disposed on the body comprising frit, feldspar, silica, kaolin, and zircon; and an antibacterial glaze layer disposed on the masking layer comprising frit, kaolin, zinc oxide (ZnO), and a color pigment, wherein the antibacterial glaze layer has antibacterial properties against both Staphylococcus aureus and Escherichia coli, and the color pigment comprises cobalt iron chromium oxide (Co(Fe,Cr)2O4). Claim 12 An antibacterial ceramic product comprising: a body comprising limestone, clay, feldspar, pyrophyllite, and kaolin; a masking layer disposed on the body comprising frit, feldspar, silica, kaolin, and zircon; and an antibacterial glaze layer disposed on the masking layer comprising frit, kaolin, zinc oxide (ZnO), and a color pigment, wherein the antibacterial glaze layer has antibacterial properties against both Staphylococcus aureus and Escherichia coli, and the color pigment comprises cobalt aluminum oxide (CoAl2O4).

Citation Information

Patent Citations

  • Optical catalyst compound, optical catalyst containing substance, optical catalyst function exerting material and method for manufacturing it

    JP2004290974A

  • Method for preparing ceramic ink comprising metal precursor and ceramic pigment and ceramic ink manufactured by the same

    KR1020180021278A

  • Manufacturing method for paint composition with excellent thermal insulation and purification

    KR1020230084768A

  • Product having photocatalystic performance and production thereof

    JP1998337477A

  • Antibacterial glaze composition and manufacturing method of ceramic tile using the composition

    KR1020220083041A